GEOMECHANICAL PROPERTIES OF PEMATANG SHALE IN KILIRANJAO SUB BASIN, SIJUNJUNG REGENCY WEST SUMATRA PROVINCE. - VIAN PRATAMA - NIM: 22016012, WAHYU
Increased energy demand and declining oil and gas production cause reducing oil and gas reserves. The more difficult the discovery of new field based on conventional hydrocarbon play, a new concept of research on non conventional hydrocarbons is required. Currently, there is no non conventional hydrocarbon play which has proven in Indonesia, but some basins are productive conventionally, for instance Central Sumatra Basin. Beside organic material richness and maturity, geomechanical properties of shale has important role in shale hydrocarbon productivity. The research area is located in Kiliranjao Sub Basin which is one of the half graben caused by Sumatra rifting in the Early Cretaceous. The data used in this study are outcrop data and laboratory test data obtained through stratigraphic cross-sectional measurements and shallow drilling. The rock samples were then processed through laboratory tests including thin section, palynology, x-ray diffraction (XRD), geochemical analysis of source rock, uniaxial compressive strength test (UCS), and ultrasonic wave test. Lithofacies of shale in the research area consists of four facies, namely Silliceous Claystone, Silty Claystone, Carbonaceous Siltstone, and Carbonaceous Shale. The geochemical analysis of shales shows TOC values with very good-excellent categories and kerogen type I-II. Based on mineralogy analysis using XRD, the brittleness index of shale is moderately brittle - brittle. Based on uniaxial compressive strength test (UCS) and ultrasonic wave test, it is known that UCS and Young modulus (static and dynamic) improving value have simillar pattern with increasing carbonate mineral content and decreasing clay minerals. Increasing carbonate mineral content cause raising brittleness index value. Then it can be concluded that there is a positive correlation between rock strength, Young modulus value, Poisson ratio, brittleness index and carbonate mineral content.